2018
DOI: 10.1080/10412905.2018.1503099
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the essential oil yield from the rhizomes of cassumunar ginger by an eco-friendly solvent-free microwave extraction combined with central composite design

Abstract: This study aimed to apply the solvent-free microwave extraction (SFME) for isolating the essential oil from the rhizomes of cassumunar ginger and study the kinetic mechanism during the extraction process by light microscopy. A central composite design was employed to evaluate the influence of the key variables including microwave power and irradiation time on the oil recovery. The optimal process conditions of SFME were irradiation of the sample at 700 W for 70 min. Microwave power had the most significant eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The chemical composition of the Zingiber cassumunar essential oil in various countries and regions has been reported. Previous studies ( Bua-in and Paisooksantivatana, 2009 ; Leelarungrayub et al., 2017 ; Sukatta et al., 2009 ; Taroeno et al., 1991 ; Verma et al., 2018 ; Yingngam and Brantner, 2018 ) have shown that rhizome of Z. cassumunar essential oil from Thailand, India, and Indonesia are mainly composed of sabinene, terpinen-4-ol, and DMPBD, which is consistent with the results of our study. However, other studies have reported major components of Z. cassumunar essential oil that are inconsistent with our findings.…”
Section: Resultssupporting
confidence: 93%
“…The chemical composition of the Zingiber cassumunar essential oil in various countries and regions has been reported. Previous studies ( Bua-in and Paisooksantivatana, 2009 ; Leelarungrayub et al., 2017 ; Sukatta et al., 2009 ; Taroeno et al., 1991 ; Verma et al., 2018 ; Yingngam and Brantner, 2018 ) have shown that rhizome of Z. cassumunar essential oil from Thailand, India, and Indonesia are mainly composed of sabinene, terpinen-4-ol, and DMPBD, which is consistent with the results of our study. However, other studies have reported major components of Z. cassumunar essential oil that are inconsistent with our findings.…”
Section: Resultssupporting
confidence: 93%
“…This could be due to the improvement of power which leads to promote the solubility and diffusion of solute components out of the solid matrix (Alara, Abdurahman, Obanijesu, Alara, & Mudalip, 2020; Yingngam, Chiangsom, & Brantner, 2020). Moreover, the elevated pressure occurred due to microwaves inside the cell wall enhances micro explosions which could release the solute (Yingngam & Brantner, 2018). The yields are starting to decrease when the power level increases beyond 420 W. This is due to the higher microwave power promotes degradation of thermo sensitive phenolic compounds (Nabet et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…3D response surface plots and contour plots were created with the developed quadratic polynomial equation in order to visualize the interaction between two independent variables and their effects on the yield of rhein. The quadratic regression model is widely used because of its universal usability in presenting different types of response surfaces [23]. From green to red, the different colors represent the increasing amount of rhein.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate and compare the impact or significance of the factor on the result, it was important to convert the real values of the level of each variable into dimensionless values. The coded units -1.68, -1, 0, +1, and +1.68 specify very low, low, intermediate, high, and very high values, respectively (Table 1) [22,23,24,31].…”
Section: Methodsmentioning
confidence: 99%